دور الإمكانات الفنيّة والبشريّة والتّنظيميّة في تبنّي نظم دعم القرار في القطّاع المصرفي (دراسة مسحيّة على المصارف في السّاحل السّوري) - نادر, نهاد; بشور, ديموتيلا (Latakia University Journal - Economic and Legal Sciences Series, 2017)
هدفت الدّراسة إلى التّعرّف على العلاقة بين الإمكانات الفنيّة، البشريّة، والتّنظيميّة من جهة، وتبنّي نظم دعم القرار في المصارف في السّاحل السّوري من جهة أخرى. استخدمت الباحثة أسلوب الحصر الشّامل لكافّة المصارف في السّاحل السّوري، حيث اعتمدت الباحثة في جمع البيانات على الاستبيان، وقامت بتوزيع(142) استبانة على عينة من العاملين في المصارف المدروسة كان صالحاً منها للتّحليل(118) استبانة. وقد خلُصت الدّراسة إلى أنّ للإمكانات الفنيّة، والبشريّة، والتّنظيميّة المتاحة، دور في تبنّي نظم دعم القرار في المصارف في السّاحل السّوري، حيث كانت النتيجة الرّئيسة الأهمّ هي امتلاك المصارف لرأس مال بشري قادر على تبنّي نظم دعم القرار، ثم تمّ عرض بعض التوصيات للتّبنّي النّاجح لنظم دعم القرار ومن أهمّها: زيادة الاهتمام بالإمكانات التّنظيميّة المتاحة من خلال ضرورة وجود وحدة مستقلة لنظم دعم القرار تتبع مباشرة للإدارة العليا في المصارف في السّاحل السّوري، والسّماح للهيكل التنظيمي بتدفق المعلومات بسهولة بين الأقسام المختلفة، زيادة الاهتمام بالإمكانات البشرية المتاحة لاستخدام نظم دعم القرار كتوفير برامج تدريبية متخصّصة للعاملين على استخدام برامج نظم دعم القرار.The study aimed to identify the relationship between the technical, human, and regulatory abilities, and the adoption of decision support system in the Syrian Coast Banks. The researcher used the comprehensive inventory of all the banks in the Syrian Coast style, and relied on a questionnaire for data collection, where she distributed (118) to identify a sample of workers in the studied banks. The study concluded that the technical, human and regulatory abilities, have a role on the adoption of decision support system in the Syrian Coast Banks, and the most important result was that the banks own human capital is able to adopt a decision support systems. Then some of the recommendations show up for successful adoption of decision support systems and most important are: increased interest in available regulatory abilities through the necessity of a separate unit for decision support systems directly linked to the senior management at the banks in the Syrian Coast, and let the organizational structure to flow the information easily between different departments, greater attention to human abilities available to use the decision support systems like: provision of specialized training programs for workers to use decision support system software.